Pembentukan Karakter Al-Quran melalui Implementasi Kurikulum Merdeka di Sekolah Dasar - Syarifah Syarifah; Ilma Mukarramatul Kubra (Academicus: Journal of Teaching and Learning, 2024)
This study aims to determine the implementation of the independent curriculum in the formation of Quranic character at SD Birrul Walidain Muhammadiyah Sragen. This study is a qualitative study with a descriptive approach conducted at SD Birrul Walidain Muhammadiyah Sragen involving curriculum teachers, student teachers and teachers who teach in the class as research subjects. Data collection techniques in this study were carried out by means of observation, interviews, and documentation and for data analysis used were data collection, data reduction, and drawing conclusions. The results of this study found that 1. The implementation of the independent curriculum in the formation of Quranic character at SD Muhammadiyah Birrul Walidain Sragen uses 3 class models, namely the Quran class, bilingual class and talent class which are divided into intracurricular, co-curricular and extracurricular activities with a holistic and structured approach that focuses on developing competencies, Pancasila values ​​and Quranic character 2. Inhibiting and supporting factors are the main keys in optimizing the implementation of the Independent Curriculum at SD Muhammadiyah Birrul Walidain Sragen and ensuring the success of the formation of students' Quranic character.